2001
DOI: 10.1046/j.1365-2621.2001.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infrared heating on the properties of legume seeds*

Abstract: Summary Five legume seeds (kidney beans, green peas, black beans, lentil and pinto beans) were heated by infrared to a surface temperature of 140 °C. The changes in chemical composition, physical, mechanical and functional properties of the processed seeds were measured and compared to those of the raw seeds. Significant changes in the properties of the seeds in terms of increased volume, lower rupture point and toughness, higher water uptake and higher leaching losses (when the seeds were soaked in water) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 15 publications
(18 reference statements)
5
74
2
Order By: Relevance
“…the effect of moisture content on the physical properties of chickpea seeds (konak et al 2002), QP-38 pigeon pea (baryeh & mangope 2002), cocoa bean (bartPlange & baryeh 2003), lentil seed (Amin et al 2004), and faba bean (Altuntas & Yildiz 2007) have been reported. several researchers have also determined the agronomic, mechanical, and thermal properties of grain legume seeds (bay et al 1996;Fasina et al 2001;Akinjayeju & bisiriyu 2004;bhattacharya et al 2005). However, studies conducted on the effect of moisture content on grain legume seeds such as kidney bean, pea, and black-eyed pea seeds have not been adequately or comparatively studied.…”
Section: Introductionmentioning
confidence: 99%
“…the effect of moisture content on the physical properties of chickpea seeds (konak et al 2002), QP-38 pigeon pea (baryeh & mangope 2002), cocoa bean (bartPlange & baryeh 2003), lentil seed (Amin et al 2004), and faba bean (Altuntas & Yildiz 2007) have been reported. several researchers have also determined the agronomic, mechanical, and thermal properties of grain legume seeds (bay et al 1996;Fasina et al 2001;Akinjayeju & bisiriyu 2004;bhattacharya et al 2005). However, studies conducted on the effect of moisture content on grain legume seeds such as kidney bean, pea, and black-eyed pea seeds have not been adequately or comparatively studied.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, [9], reported that, the mean diameter and thickness of lentil were 4.45-6.82 and 2.36-2.55 mm respectively. Table 3 shows Pearson correlation coefficients among quantitative characters; SDM and WHS were positively and significantly correlated.…”
Section: Descriptive Statistics and Analysis Of Correlations (Pearsonmentioning
confidence: 96%
“…1A). This can be due partially to protein denaturation and starch gelatinization (Fasina et al 2001). The denaturation of proteins caused structural differences leading to porosity; in addition, changes in amylopectin-amylose relationship occurred (Zhen et al 2011).…”
Section: Physicochemical Properties Of Tempeh Bean Flourmentioning
confidence: 99%